Effects of Kakato‐tsurutsuru socks on dry heels in healthy volunteer subjects - Kamo, Atsuko; Umehara, Yoshie; Negi, Osamu; Iwata, Makoto; Kamata, Yayoi; Suga, Yasushi; Ogawa, Hideoki; Tominaga, Mitsutoshi; Takamori, Kenji (Journal of dermatology, 2020)
Kakato‐tsurutsuru (Kt) socks have been selling for almost 30 years in Japan. Wearers claim they improve heel dryness despite no scientific evidence. We investigated the effects of Kt socks on heel dryness by questionnaire, clinical scores and non‐invasive skin measurements. In a double‐blind, randomized cross‐over study, 10 healthy volunteers wore control or Kt socks over 2 weeks in sequence for 4 weeks. Skin hydration and evaporation of the medial and dorsal heel were measured before and every week during the trial. Clinical evaluations of desquamation and cracked skin were scored by a dermatologist. A visual analog scale (VAS) questionnaire of comfort, sock climate humidity and skin dryness was conducted. The VAS of comfort was significantly higher in Kt than controls. Average Δskin dryness in control and Kt groups was −1.63 and 2.22, respectively, showing a significant improvement. In the clinical findings of the dorsal side of the heel, Δdesquamation and Δcracked skin scores were significantly decreased and Δstratum corneum hydration significantly increased in Kt compared with controls. Kt socks may retain evaporated sweat with components of natural moisturizing factors, supporting the water‐holding ability of the heel stratum corneum. These findings suggest that Kt socks may improve heel skin dryness.